2006
DOI: 10.1007/bf03174974
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperbaric oxygenation on thein vitro growth ofEscherichia coli in environments with and without blood cells

Abstract: The aim of this study was to investigate whether the in vitro presence of blood cells influences the anti-microbial activity of hyperbaric oxygen (HBO) against Escherichia coli. Fifty E. coli isolates from clinical samples were used in the study. A small number of colonies belonging to each isolate from the nutrient media were transferred into two K 3 EDTA tubes (the blood group) and two Mueller-Hinton broth tubes (the broth group). Then, both groups were divided into subgroups according to whether HBO was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Other studies have documented the antibacterial effects of HBO [20, 30]. Turhan et al [20], reported that HBO therapy alone or in combination with either linezolid, teicoplanin or vancomycin was effective in treating mediastinitis caused by MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have documented the antibacterial effects of HBO [20, 30]. Turhan et al [20], reported that HBO therapy alone or in combination with either linezolid, teicoplanin or vancomycin was effective in treating mediastinitis caused by MRSA.…”
Section: Discussionmentioning
confidence: 99%